2015
DOI: 10.1016/j.ymgmr.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Insights in the etiopathology of galactosyltransferase II (GalT-II) deficiency from transcriptome-wide expression profiling of skin fibroblasts of two sisters with compound heterozygosity for two novel B3GALT6 mutations

Abstract: Mutations in B3GALT6, encoding the galactosyltransferase II (GalT-II) involved in the synthesis of the glycosaminoglycan (GAG) linkage region of proteoglycans (PGs), have recently been associated with a spectrum of connective tissue disorders, including spondyloepimetaphyseal dysplasia with joint laxity type 1 (SEMDJL1) and Ehlers–Danlos-like syndrome. Here, we report on two sisters compound heterozygous for two novel B3GALT6 mutations that presented with severe short stature and progressive kyphoscoliosis, jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…A microarray-based transcriptome analysis of skin fibroblasts from two individuals with mutations in this gene has revealed the pronounced downregulation of COMP, which is accompanied by alterations in the secretion and matrix assembly of collagen I and collagen III, eventually leading to hyperextensible skin (Ritelli et al, 2015). These changes in the biomechanical properties of the skin of such individuals are reminiscent of the softer skin that we observed in COMP-deficient mice.…”
Section: Discussionmentioning
confidence: 64%
“…A microarray-based transcriptome analysis of skin fibroblasts from two individuals with mutations in this gene has revealed the pronounced downregulation of COMP, which is accompanied by alterations in the secretion and matrix assembly of collagen I and collagen III, eventually leading to hyperextensible skin (Ritelli et al, 2015). These changes in the biomechanical properties of the skin of such individuals are reminiscent of the softer skin that we observed in COMP-deficient mice.…”
Section: Discussionmentioning
confidence: 64%
“…Following the identification of B3GALT6 as the causal gene for SEMD‐JL1, Vorster et al [] identified the same mutations and a novel p.(Thr79Ala) mutations, all located in or in the vicinity of the stem region, in eight prototype South African families. A few additional patients with an EDS/SEMDJL1 overlap phenotype have also been reported [Sellars et al, ; Ritelli et al, ; Alazami et al, ].…”
Section: Spondylodysplastic Eds Due To β3galt6‐deficiency (Speds‐b3gamentioning
confidence: 99%
“…The molecular basis of these observations remains to be established. In two patients harboring a compound deletion and catalytic domain mutation [Ritelli et al, ] showed by micro‐array transcriptome and immunofluorescence analyses a reduced expression of cartilage oligomeric matrix protein ( COMP ) and osteopontin ( SPP1 ). Interestingly, these authors reported reduced expression and disassembly of HS GAG chains and of the HS‐matrix PG perlecan.…”
Section: Spondylodysplastic Eds Due To β3galt6‐deficiency (Speds‐b3gamentioning
confidence: 99%
“…To investigate the pathogenic effects of the c.618C > G, p.(Cys206Trp) variant, as well as 12 other selected missense pathogenic variants spanning the β3GalT6 protein (NP_542172.2) (Table ): c.16C > T, p.(Arg6Trp); c.193A > G, p.(Ser65Gly); c.200C > T, p.(Pro67Leu); c.466G > A, p.(Asp156Asn); c.694C > T, p.(Arg232Cys); c.899G > C, p.(Cys300Ser); c.925 T > A, p.(Ser309Thr); c.235A > G, p.(Thr79Ala); c.476C > A, p.(Ser159Tyr); c.795A > C, p.(Glu265Asp); c.556 T > C, p.(Phe186Leu) and c.766C > T, p.(Arg256Trp) . These variants were generated by site‐directed mutagenesis (Pfu UltraHF cat#600384‐51) using cMyc‐tagged B3GALT6 ‐pCMV6 plasmid (RC223942; OriGene, Rockville, MD) as template.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the pathogenic effects of the c.618C > G, p. (Arg256Trp). 16 These variants were generated by site-directed mutagenesis (Pfu UltraHF cat#600384-51) using cMyc-tagged B3GALT6-pCMV6 plasmid (RC223942; OriGene, Rockville, MD) as template. All primers were listed in Table S1, Supporting Information and generated variants were systematically confirmed by Sanger sequencing.…”
Section: Generation Of Variant Expression Constructsmentioning
confidence: 99%